2014
DOI: 10.1371/journal.pone.0090537
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration Networks from a Large CV Database: Dynamics, Topology and Bonus Impact

Abstract: Understanding the dynamics of research production and collaboration may reveal better strategies for scientific careers, academic institutions, and funding agencies. Here we propose the use of a large and multidisciplinary database of scientific curricula in Brazil, namely, the Lattes Platform, to study patterns of scientific production and collaboration. Detailed information about publications and researchers is available in this database. Individual curricula are submitted by the researchers themselves so th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 54 publications
1
17
0
1
Order By: Relevance
“…5 Physicists have combined complex network theory (Barabási & Albert, 1999;Watts & Strogatz, 1998) and collaborative filtering (CF) (Herlocker et al, 2004;Schafer et al, 2007) in an attempt to create better recommendation engines in social networks and the principles of physical dynamics, including mass diffusion (Zhou et al, 2007), and heat conduction , have been applied in a CF algorithm. A popular approach has been to construct recommendation data via a user-object bipartite network where the nodes are divided into two sets, but only connections between two nodes in different sets are allowed (Araújo et al, 2014;Estrada & Rodriguez-Velazquez, 2005;Li & Chen, 2013;Lind et al, 2005;Ramasco et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…5 Physicists have combined complex network theory (Barabási & Albert, 1999;Watts & Strogatz, 1998) and collaborative filtering (CF) (Herlocker et al, 2004;Schafer et al, 2007) in an attempt to create better recommendation engines in social networks and the principles of physical dynamics, including mass diffusion (Zhou et al, 2007), and heat conduction , have been applied in a CF algorithm. A popular approach has been to construct recommendation data via a user-object bipartite network where the nodes are divided into two sets, but only connections between two nodes in different sets are allowed (Araújo et al, 2014;Estrada & Rodriguez-Velazquez, 2005;Li & Chen, 2013;Lind et al, 2005;Ramasco et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…4c). Second, the number of papers authored by a scientist follows a power-law distribution with exponential cutoff [56,57] ( Supplementary Fig. S5b).…”
mentioning
confidence: 99%
“…However, the analysis of the collaboration networks showed that Brazil had the highest number of authors and groups working in 'population genetics of Neotropical plants', which followed the general trend of an increase in research and collaboration networks in recent decades (Araújo et al, 2014). Thus, the highest number of authors is not only an effect of human resource development abroad but is also because of the expansion of graduate programs and research funding over the last decade (Leta et al, 1998;CAPES, 2004).…”
Section: Discussionmentioning
confidence: 99%